I19 Normalization of phenotype and reduction of gliosis levels via glutaminyl cyclases inhibition in a huntington disease mouse model. (September 2018) - Plank, Anne-Christine; Schilling, Stephan; Hoffmann, Torsten; Lues, Inge; Hörsten, Stephan von
Abstract : Background: Huntington disease (HD) may be aggravated by enzymatic activity of glutaminyl cyclase (QC/QPCT) and its isoenzyme (isoQC/QPCTL) via the following mechanisms: Neurotoxic pyroglutamated (pGlu) mutant huntingtin (mHTT) fragments may be formed via N-terminal glutamine cyclization of truncated mHTT species by enzymatic activity of QC and/or isoQC. Subclinical neuroinflammation and gliosis in HD may be triggered via isoQC-dependent maturation of pGlu-CCL2. QC-associated interference in heat shock protein and chaperone levels may promote mHTT cellular toxicity. Aims: The present study sought to investigate the role of QC/isoQC in HD via genetic and pharmacological proof-of-concept (POC) experiments targeting the (iso)enzyme in the BACHD mouse model of HD. Methods: Genetic POC was achieved by crossbreeding of BACHD with QC-KO/isoQC-KO mice, pharmacological POC by early interventional studies in 6-weeks-old BACHD mice for 18 weeks using increasing dosages of the QC/isoQC inhibitor PQ912 (Probiodrug AG). Several behavioral and physiological end-points including cellular and morphological markers were examined. Results: PQ912 treatment resulted in lowered mHTT and GFAP levels, associated with normalization of the abnormal body weight gain and energy metabolism of BACHD mice at 24 weeks of age. PQ912 treatment was well tolerated in a wide range of dosages with no obvious adverse effects. Crossbreeding of iso/QC-KO mice ameliorated the body weight increase and certain behavioral abnormalities in BACHD mice. Conclusion: Experiments provide evidence for glutaminyl cyclases to represent a druggable target in HD. Early QC/isoQC-inhibitor-based pharmacological intervention in BACHD mice resulted in clear beneficial effects, including but not limited to a lowering of mHTT. Since the QC/isoQC inhibitor PQ912 is in clinical development for the indication AD, further preclinical and translational studies in HD are tempted.